Uma solução de integração da monitoração em redes para experimentação baseada na OML e perfSONAR - MACEDO, Igor Leonardo Eloy (2014)
The internet as it is used today, already has many deficiencies and problems, leading to the elaboration and implementation of new protocols and services in order to achieve a better performance. Because of this, the amount of groups focused in research on new technologies for global data communication, ie, research on Future Internet (FI), has increased. In parallel, aiming to provide infrastructure for testing of new communication technologies, there are experimental networks. They are based on software and provided by testbeds like GENI, NitLab and FIBRE, among others, delivering a robust and flexible infrastructure for their users. From the architectural point of view, the testbed FIBRE intends to be a complete solution based on the integration and/or federation of CMFs. Maintained by institutions around the world (Brazil, Europe, Australia), incorporates various control and management technologies (CMF - Control and Management Frameworks), such as OMF, ProtoGENI and Ofelia. The diversity in the use of these experimental network managers in the same testbed, demanded the integration of the orchestration and monitoring of data's experiments. In order to integrate the monitoring data, the MDIPs (Measurement Data Integration Point), a specific solutions for each CMF, have the common goal of converging all monitoring data in a common format, making use of perfSONAR standards and protocols. Based on the same concept, the OML MDIP, object of this dissertation work, has the ability to converge the data captured by OML (OMF´s monitoring tool) in a common format, ensuring ease access and data portability for FIBRE users. The OML MDIP, as developed, can export data from a OML Server, as a standardized format, compatible with perfSONAR, aiming at integration of monitoring data, in addition to enableaccess to monitoring data, in a distributed way, through its integration with iRODS tools.